Investigating the Effect of Different PWM Modes on Ripple Reduction in Five-Phase BLDC Motor with New Method - Seyed Mohsen Mirbagheri; Seyed Sajjad Salehi GHalehsefid; Seyed Mohammad Hossein Mousavi (Institute of Advanced Engineering and Science, 2014)
Torque ripple is one of the main drawbacks of brushless DC motors. in the case of three phase motors, PWM modes have a significant effect on the generated torque ripple. So, like three phase BLDC motors, we investigate the effect of different PWM modes on torque ripple of five-phase BLDC motor that has less torque ripple in high speed. in this investigation we will show that freewheeling current in inactive phase is important factor in torque ripple. Also simulation in matlab/Simulink prove this event.